Some Preliminary Results of the Synthesis and Investigation of the Glass/FTO/Si/Au/ Embedded Thin Film for Application in the Modified Plasmonic Solar Cell - Tien Thanh, Nguyen; Tien Thanh, Dao; Si Hieu, Nguyen; Thi Mai Huong, Nguyen (VNU Journal of Science: Mathematics - Physics, 2021)
This paper outlines the synthesis of the glass/FTO/Au/ and of the glass/FTO/Si/Au/ nanoparticles embedded thin films and then outlines some obtained experiment results concerning their properties of surface morphology, structure, chemical composition and optical absorption in comparison. Based on the measured results of SEM, EDX, XRD and UV-VIS spectroscopy we observed that the structure of the sputtered Si layer is amorphous phase meanwhile the structure of the sputtered Au layer is crystallized phase. Depending on the sputtered layers (Si, Au) thicknesses and technological conditions the different surfaces morphologies of the Au flat surface layer or the Au bumpy surface layer with different sizes of nanoparticles /clusters are formed on both the samples surfaces of FTO and amorphous Si layers. Notably, the optical absorption spectra of glass/FTO/Si/Au thin film in both cases of thermal annealing and without thermal annealing are significantly enhanced and shifted to blue- and red regions, these results can be explained by the role of the amorphous Si layer, as well as the Si/Au Schottky layers/nanoparticles barrier configurations caused. The glass/FTO/Si/Au layer/nanoparticles thin films could be used for integration with the core structure (Au/TiO 2 ) of plasmonic solar cell for aiming to  enhance the solar cell performance.